Niveles de fertilización orgánica en la producción forrajera y composición química de moringa (moringa oleífera) - Cedeño Arriaga, Estela Cristina (2022)
The research was carried out at the “La María” Campus of the State Technical University of Quevedo. The objective of the research was to evaluate the effect of different doses of compost on the agronomic variables and chemical composition of Moringa oleifera during the dry season. Four treatments were evaluated; (0, 770, 1540, 2310 g compost/plant-1), with four repetitions. The harvest was carried out 60 days after the application. A completely randomized design (DCA) was used. The variables evaluated within the agronomic parameters were (AP, PH, PT, RHT, TAC, biomass and production/Ha), for the nutritional quality the variables (DM, MO, PC, FDN, FDA) were evaluated. In the results obtained it was possible to know that there was no significant difference between the treatments. Within the agronomic behavior both for plant height and leaf weight, the highest value was obtained in T2, for stem weight, forage biomass and forage production, the best record corresponded to T0. Regarding the bromatological composition, the highest DM content was obtained in T2, in MO T3, the PC value was T2 in FDN and FDA was recorded in T1. It is concluded that organic fertilization did not have a major influence on the agronomic performance and nutritional parameters at 60 days of cutting. It is recommended to evaluate the effect of organic fertilizer at higher cutting age and in the rainy season.